2012
DOI: 10.2478/s11687-012-0048-4
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal and fertilizing effects of chicken manure, fresh and composted olive mill wastes on organic melon

Abstract: The fertilizing and nematicidal effects of three organic amendments were evaluated in a pot experiment on melon plants infested by the root-knot nematode Meloidogyne incognita. A soil artificially infested with 4 eggs and juveniles/ ml soil of the nematode was amended with: a) virgin olive pomace (VOP); b) composted olive pomace (COP); c) chicken manure based fertilizer (CM) and d) chicken manure based fertilizer combined with the biological control agent Paecilomyces lilacinus strain 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…Generally speaking, the present open field experiment confirmed the nematological results obtained by Abdel-Dayem et al (2012) in pot trials. The containment of the RKN population density of the treated plots to almost the initial value could be ascribed to the release of ammonia from CM and polyphenols and fatty acids from VOP and COP, as reported by several Authors (e.g., Cayuela et al, 2008;Renčo et al, 2010Renčo et al, , 2011.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Generally speaking, the present open field experiment confirmed the nematological results obtained by Abdel-Dayem et al (2012) in pot trials. The containment of the RKN population density of the treated plots to almost the initial value could be ascribed to the release of ammonia from CM and polyphenols and fatty acids from VOP and COP, as reported by several Authors (e.g., Cayuela et al, 2008;Renčo et al, 2010Renčo et al, , 2011.…”
Section: Discussionsupporting
confidence: 93%
“…In a previous paper, Abdel-Dayem et al (2012) carried out an experiment in pots artificially infested by Meloidogyne incognita at a population density of four eggs and juveniles mL −1 : Authors tested, on melon seedlings, the nematicidal and growth effects of virgin olive pomace (VOP) and an olive pomace based compost (COP), both at three different doses, in comparison to chicken manure, applied alone (CM) and in combination to Paecilomyces lilacinus strain 251 (CBM), a nematophagous fungus with the capacity to parasitize unspecified nematodes at all stages of their life cycles (Dong and Zhang, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The mode of action of chicken manure is thought to be based on the release of toxic levels of ammonium, although alterations in soil structure, the stimulation of antagonistic organisms, and improved plant tolerance also may play a role (Lazarovits et al, 2001 andLopez-Pérez et al, 2005). Abdel-Dayem et al, (2012) showed that the lowest root gall index of the nematode was achieved with chicken manure treatment and had a toxic effect on M. incognita by release the high amount of ammonium. The effectiveness of chicken manure depends on neutral pH, a high N content and a narrow C/N ratio (C/N=5.6).…”
Section: Discussionmentioning
confidence: 99%
“…On olive, tomato, lettuce, strawberry and white button mushroom, Nair et al (2014) claimed that humified compost prepared from olive mill solid waste significantly increased total organic carbon and humic substances by 40 and 58 %, respectively in the soil and enhanced crop productivity. Incorporation organic wastes into the soil after an appropriate composting process can improve plant resistance to nematode and fungi attack by stimulating root development and plant growth because of their large content of nutritive elements (Sasanelli et al 2011;D`Addabbo et al 2012;Abdel-Dayem et al 2012 andAbdel-Dayem et al 2014). Also can act as a method for weed control (Boz et al, 2009), for improving soil fertility, water-holding capacity and physical and chemical properties (Cucci et al, 2013;Bueno et al, 2014 andKilli et al, 2014), and finally its impact on ground water was the minimum compared to mineral fertilizers (Caputo et al, 2013).…”
Section: Itroductionmentioning
confidence: 99%